The impact of business ethics behaviour on the customers’ loyalty in beauty industry among university students’ in Malaysia / Nareesa Noorham, Sharifah Nurafizah Syed Annuar and Hasnawati Guliling - Noorham, Nareesa; Syed Annuar, Sharifah Nurafizah; Guliling, Hasnawati (UiTM Cawangan Johor, 2020)
The beauty industry had humble beginnings, starting from centuries ago, the perceptions on beauty products fluctuated from being used only by the wealthiest of people to be a completely taboo subject. In recent years, the beauty industry has been incriminated because of the business practice which includes unethical behavior such as the use of harmful ingredients, animal testing, child labour and excessive advertising. This study will be done by using an existing research articles and the data will be collected using questionnaire. Thus, this study aims to determine the relationship between business ethics behaviour towards customers’ loyalty. This study is useful to determine the impact of business ethics behaviour which influences customers’ loyalty in the beauty industry. A proposed framework and implementation will be presented in this paper.